2011
DOI: 10.1002/art.30650
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel recombinant biotherapeutic with applications in targeted therapy of human arthritis

Abstract: Objective. To isolate recombinant antibodies with specificity for human arthritic synovium and to develop targeting reagents with joint-specific delivery capacity for therapeutic and/or diagnostic applications.Methods. In vivo single-chain Fv (scFv) antibody phage display screening using a human synovial xenograft model was used to isolate antibodies specific to the microvasculature of human arthritic synovium. Singlechain Fv antibody tissue-specific reactivity was assessed by immunostaining of synovial tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…The next step in increasing the therapeutic potency and the safety profile would be the development of tissue-specific (not only inflammation-specific) targeting agents (32). With regard to RA synovium, our group of investigators has previously identified peptides and scFv antibody fragments with selective specificity for the synovium (45)(46)(47). The incorporation of the scFv A7 in the aDVD format, as demonstrated herein for ICAM-1, will provide specificity for human arthritic synovium to the molecule, with great potential for tissue-specific drug delivery in RA.…”
Section: Discussionmentioning
confidence: 99%
“…The next step in increasing the therapeutic potency and the safety profile would be the development of tissue-specific (not only inflammation-specific) targeting agents (32). With regard to RA synovium, our group of investigators has previously identified peptides and scFv antibody fragments with selective specificity for the synovium (45)(46)(47). The incorporation of the scFv A7 in the aDVD format, as demonstrated herein for ICAM-1, will provide specificity for human arthritic synovium to the molecule, with great potential for tissue-specific drug delivery in RA.…”
Section: Discussionmentioning
confidence: 99%
“…The use of fresh human tissues ( ex vivo ) [2831]or mouse models ( in vivo ) [7,8,28,32,33]for phage selection enhances the possibility of finding a peptide/antibody that can bind to human tissues in vivo , improving the diagnosis of the associated diseases. Such strategies have been successfully employed for tumors [28], and even for atherosclerosis [32,34].…”
Section: Discussionmentioning
confidence: 99%
“…As a follow-up study, the same group developed an antibody specific to human inflamed synovium in xenografted severe combined immunodeficiency mice termed A7 [20]. A7 scFv bound the microvasculature of RA, OA, Crohn's disease, and psoriatic skin sections, but not normal tissues (including normal synovium).…”
Section: Other Targeted Therapeuticsmentioning
confidence: 97%